(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The scientific article provides a brief analysis of the judicial and legal reform carried out in the Kyrgyz Republic in the area of prevention and prevention of domestic violence. In addition, factors that hinder the effective fight and prevention of domestic violence by internal affairs bodies are reflected.